The Impact of Digital Economic Dimensions on the Stability and Efficiency of Monetary Policy in Indonesia: Quantitative Analysis in the Era of Digital Transformation - Selfia Putri Johana Eka Ningsih Simatupang; Rusiadi Rusiadi; Lia Nazliana Nasution (Journal Economic Excellence Ibnu Sina, 2025)
This study uses quantitative analysis in the age of digital transformation to ascertain how Indonesia's monetary policy's stability and effectiveness are affected by digital economic characteristics. The Simultaneous Regression approach (also known as structural regression) with two simultaneous equations—monetary stability and monetary policy effectiveness—is the data analysis technique used in this study. Monetary stability (SM), the volume of digital transactions (VTD), the number of digital service users (PLD), financial technology adaptation (ATF), monetary policy effectiveness (EKM), e-commerce growth (PEC), and digital financial inclusion (IKD) are the variables considered in this study. The findings indicate that the variables VTD, PLD, ATF, and EKM have a 62.3% influence on the SM variable, with other variables outside the estimation accounting for the remaining 37.7% of SM. The estimation results show that the Effectiveness of Monetary Policy (EKM) can be explained by the Digital Financial Inclusion (IKD) and Monetary Stability (SM) variables by 11.7% and 88.3%, respectively. Aside from the estimations in the model, additional factors also affect the Effectiveness of Monetary Policy (EKM).